Precision medicine in the multiple sclerosis clinic: Selecting the right patient for the right treatment. (April 2020) - Bose, Gauruv; Freedman, Mark S
Multiple sclerosis (MS) is a chronic, inflammatory disease of the central nervous system (CNS), affecting patients of all ages, causing neurologic disability if inadequately treated. Some patients have a relatively benign disease course without significant disability after decades, while a more aggressive course ensues in others and disability progression occurs after only several years. Certain risk factors confer a higher chance of a patient having aggressive MS. Currently over 15 disease-modifying treatments (DMTs) are approved for MS with different efficacy and safety profiles. Deciding which DMT to use in a specific patient requires a careful analysis of a patient's disease course for high-risk factors for early progression, consideration of the efficacy and safety profile for potential therapy, as well as understanding of a patient's lifestyle and expectations. The integration of these factors is the art of precision medicine, a necessary practice in the treatment of patients with MS.